Tempo de Correspondências - Da obra de Lya Luft a um pensamento clínico: nexos e desmontes - Rochael, Patrícia (2006)
How can one seek and outline some finesse of handling in a game where not only are the partakers literary fragments, but also - implicitly or explicitly - ideas and even intensifications of the subjectivity? This has been the triggering problematization which has insisted and kept itself present during this study. From the tracking and research of Lya Luft's work, some volumes and characters have remained. We have dedicated ourselves to exploring - in these figures - some deadlocks at the induction of more life in their life spaces. They are figures acting as devices, nexuses and dismounts, shifting from solely literary contexts and telling us about some force struggles which are very interesting to clinical studies. Fragile health undertakings. Inapprehensible yet irreducible instabilities. Varying levels of sinking inherent to varying degrees of convalescence: a clinical intricacy. During the structuring of this journey a sustenance net has extended its contributions as well as conceptual and affective sparkles